Autism spectrum disorder, very-early onset schizophrenia, and child disintegrative disorder: the challenge of diagnosis. A case-report study - Di Luzio, Michelangelo; Guerrera, Silvia; Pontillo, Maria; Lala, Maria Rosaria; Casula, Laura; Valeri, Giovanni; Vicari, Stefano (Frontiers in Psychiatry, 2023)
Background: The Autism Spectrum Disorder (ASD) in Diagnostic and Statistical Manual of Mental Disorders Fifth Edition (DSM-5) contains several disorders previously present as distinct diagnoses in DSM Revised Fourth Edition (DSM-IV-TR). These include Child Disintegrative Disorder (CDD). The latter presents typical features such as a late regression of developmental acquisitions. However, it also shows symptoms similar to ASD and psychotic symptoms such as very-early onset schizophrenia (VEOS) are described in the literature. Case Report: In this case report we deepen the case of P. a child who presents a late regression, at 7 years old, associated with psychotic symptoms in the absence of organic alterations. The child was treated with antipsychotic drug therapy and cognitive-behavioral therapy. P. was diagnosed as ASD with acute and late regression associated with psychotic symptoms. During the follow-up there was a gradual improvement of the clinical conditions. Improvements possible due to therapeutic intervention (pharmacological and psychotherapeutic) and/or the natural course of the disorder. Conclusions: The diagnostic difficulty of this case reflects a clinical complexity in which it is not easy to distinguish between neurodevelopmental and psychiatric aspects. Clinical cases such as that of P. emphasize the theme of the neurodevelopment continuum model in which neurodevelopmental and psychiatric disturbs can be considered within a pattern of pathological continuity.